2012
DOI: 10.1002/ar.22434
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Morphological Variations and Age‐Related Changes of the Seminal Vesicle of Viscacha (Lagostomus maximus maximus): An Ultrastructural and Immunohistochemical Study

Abstract: The viscacha is a seasonal rodent that exhibit an annual reproductive cycle with periods of maximum reproductive activity and gonadal regression. We studied seasonal variations in the morphology and cellular population of the seminal vesicles (SVs) during both periods and in impuber animals. Seminal vesicles were studied by light and electronic microscopy. Measurements of epithelial height, nuclear diameter, luminal diameter, and muscular layer were performed. Also, we studied the distribution of androgen rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
3
10
0
2
Order By: Relevance
“…Staining intensity was stronger in luminal cells than in basal cells. This result is in agreement with previous studies (Prins et al 1991;Kimura et al 1993;Chaves et al 2012). The presence of AR in basal cells in the prostate and seminal gland is controversial; some investigators have demonstrated that AR is detectable in basal cells (Takeda et al 1990;Prins et al 1991;Kimura et al 1993;Iwamura et al 1994;Janssen et al 1994;Prins and Birch 1995) while others detected no AR in these cells (de Winter et al 1990;de Winter et al 1991;Prins et al 1991;Prins and Birch 1995).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Staining intensity was stronger in luminal cells than in basal cells. This result is in agreement with previous studies (Prins et al 1991;Kimura et al 1993;Chaves et al 2012). The presence of AR in basal cells in the prostate and seminal gland is controversial; some investigators have demonstrated that AR is detectable in basal cells (Takeda et al 1990;Prins et al 1991;Kimura et al 1993;Iwamura et al 1994;Janssen et al 1994;Prins and Birch 1995) while others detected no AR in these cells (de Winter et al 1990;de Winter et al 1991;Prins et al 1991;Prins and Birch 1995).…”
Section: Discussionsupporting
confidence: 92%
“…The presence of AR has been demonstrated in prostate and seminal vesicle cells from several species using biochemical (Sar et al 1990;Takeda et al 1990;Prins et al 1991;Janssen et al 1994;Yamashita 2004) as well as autoradiographical (Stumpf and Sar 1976;Peters and Barrack 1987) approaches. In these glands, AR has been shown to be localised in the nucleus of luminal epithelial cells (Prins et al 1991;Prins and Birch 1995), basal cells (Takeda et al 1990;Prins et al 1991;Kimura et al 1993;Iwamura et al 1994;Janssen et al 1994;Prins and Birch 1995) smooth muscle cells (Prins et al 1991;Janssen et al 1994;Prins and Birch 1995;Chaves et al 2012;Iwamura et al 1994;Kimura et al 1993;Banerjee et al 2001) and fibroblasts (Prins et al 1991;Iwamura et al 1994;Chaves et al 2012) in immunohistochemical studies. The presence of AR in basal cells is controversial.…”
mentioning
confidence: 99%
“…For example, both the seminal vesicles and prostate exhibit marked changes in size and function in animals that are classified as photoperiod-sensitive seasonal breeders [183,184]. The changes in these organs are, however, secondary to alterations in androgen synthesis and secretion which, in turn, are regulated by pituitary gonadotropins.…”
Section: Melatonin: Male Reproductive Healthmentioning
confidence: 99%
“…Besides androgen, oestrogen has also been reported to play significant roles in the accessory sex glands [11,19,24]. According to Ellem and Risbridger [14] although some rapid non-genomic oestrogen signalling are now being identified, the effect of oestrogen on the accessory gland particularly the prostate gland, under normal and prostatic disease conditions are principally mediated via the two oestrogen receptors (ERa and b).…”
Section: Introductionmentioning
confidence: 99%